Resource Control Strategies Inventory: Adaptation in Chilean Preadolescents - Franco Chalco, Eduardo (2021)
Resource Control Theory (Hawley, 1999) has been presented as an alternative theory for the study of preadolescent social behavior. However, there are no instruments to assess its proposals for the Spanish language. The study’s objective was to validate the Resource Control Resources Inventory for the Chilean preadolescent population. For this purpose, qualitative and quantitative methodologies were used. 5th to 8th graders from two public schools from Santiago de Chile were part of the sample. Seven students were interviewed, and 180 were surveyed. After the translation and adaptation, the inventory showed an excellent fit to the factorial model, and the criterion validity showed similar results to those reported in recent literature.